Reversal of cisplatin triggered neurotoxicity by Acacia hydaspica ethyl acetate fraction via regulating brain acetylcholinesterase activity, DNA damage, and pro-inflammatory cytokines in the rodent model - Tayyaba Afsar; Suhail Razak; Ali Almajwal (BMC, 2022)
Abstract Background Cisplatin (CisPT) is a chemotherapeutic that outcome in adverse effects including neurotoxicity. We examined the efficacy of hydaspica ethyl acetate extract (AHE) against CisPT-prompted neurotoxicity. Methods Group I: Distilled water; Group II: CisPT (12 mg/kg b.w. i.p) on the 13th day of treatment. Group III: received AHE (400 mg/kg b.w) orally for 16 days. Group IV and V received 200 and 400 mg/kg b.w AHE orally for 16 days while CisPT injection on day 13, respectively. Group VI: received Silymarin (100 mg/kg b.w) orally for 16 days and CP (12 mg/kg b.w., i.p.) on day 13. TNF-α, IL6, brain acetylcholinesterase activity (AChE), oxidative trauma markers, genotoxicity, antioxidant enzymes, and morphological alterations in cerebral hemispheres were inspected. Results AHE administration before CisPT considerably reduced both tissue TNF-α and IL 6 expressions compared to CisPT treated group in a dose-dependent manner. AHE treatment (400 mg/kg b.w) significantly ameliorated brain AChE activity. Brain tissue MDA, H2O2, and NO content were markedly (p < 0.001) elevated after CisPT inoculation while a noticeable (p < 0.001) diminution was observed in AHE treatment groups. AHE treatment significantly (p < 0.001) improved brain antioxidant defense in a dose-dependent manner. Furthermore, AHE efficiently recused CisPT to induce DNA damage in brain tissue as revealed by ladder assay and DNA fragmentation patterns. Histopathological findings revealed severe neurodegenerations in CisPT treated group, however, AHE treatment noticeably precluded morphological alterations and neuron damages induced by CisPT. Conclusion A. hydaspica AHE extract may be provided as a prospective adjuvant that precludes CisPT-induced neurotoxicity due to its radical scavenging and antioxidant potential.